Theocritus and the archaeology of Greek poetry - Hunter, Richard L. 1953- (Cambridge Univ. Press, 1996)
The poems of Theocritus are our best witness to a brilliant poetic culture that flourished in the first half of the third century BC. This book considers the context from which these poems grew and, in particular, the manner in which they engage with and recreate the poetic forms of the Greek archaic age. The focus is not on the familiar bucolic poems of Theocritus, but on the hymns, mimes and erotic poems of the second half of the corpus. Recent papyri have greatly increased our understanding of how Theocritus read archaic poetry, and these discoveries are fully exploited in a set of readings which will change the way we look at Hellenistic poetry